Peningkatan Motivasi dan Hasil Belajar Agama Islam Melalui Metode Penugasan dan Resitasi pada Siswa Sekolah Menengah Pertamna di Balikpapan - Alimuddin Alimuddin (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
The purpose of this research is to increase motivation and recitation. This study used a classroom action research design. The research subjects were students of class IX totaling 22 students. The results showed that there was a significant increase in the learning activities of the subject matter of faith in students’ final day gradually. Process evaluation shows an increase in the effectiveness of teacher directions on the activities carried out and the abilities mastered by students. Evaluation of student learning outcomes shows an increase toward completeness in cycle 1 reaching the sufficient category (68.18%) and cycle 2 reaching the good category (77.27%), and cycle 3 reaching the very good category (86.36%). It is recommended that the principal of the school be able to encourage and foster teachers to strive to improve understanding of Islamic religious learning in the last day and its implementation in class.